NIVEAU D’ETUDE DES PERES ET FORMES D’AGRESSIVITE CHEZ DES ELEVES PREADOLESCENTS DE CM (CAS DE L’EPP CITE DES ARTS) - N’guessan Assandé Gilbert (European Scientific Journal, ESJ, 2013)
Our investigation aims to study the relationship between forms of aggression preteens students and the level of education of their fathers. For this purpose, fifty-four (54) all children in the classroom Middle Course (CM) , 27 students have fathers level of primary research and 27 fathers of higher level of education were examined. These subjects were ageded between 9 and 12 years, and they live with their biological fathers. For data collection, we used a questionnaire adapted to measure forms of aggression Little, Brauner, Jones, Hawley (2003). The results of our research show that there is a significant difference between the two groups of subjects with regard to forms of aggression studied. The alternate assumptions are confirmed. In other words, physical aggression is more common among those whose fathers have a primary level compared to their counterparts whose fathers have a higher level of education study. In contrast, relational aggression is more common among those whose fathers have a higher level of education compared to those whose fathers have a primary-level study. These results confirm the theories of social learning.